(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: Biometric acknowledgment frameworks have progressed altogether in the most recent decade and their utilization in explicit applications will increment sooner rather than later. The capacity to direct important correlations and evaluations will be urgent to fruitful organization and expanding biometric selection. Indeed, even the best methodology and unimodal biometric frameworks couldn’t completely address the issue of exactness and execution as far as their bogus acknowledge rate (FAR) and bogus oddball rate (FRR). In spite of the fact that multimodal biometric frameworks had the option to moderate a portion of the restrictions experienced in unimodal biometric frameworks, like non-all inclusiveness, uniqueness, non-adequacy, loud sensor information, parody assaults, and execution, the issue of low exactness actually continues. In this paper, we survey research papers zeroed in on the precision improvement in data combination of face and finger impression biometric acknowledgment frameworks, decide the primary highlights of the chose techniques, and afterward call attention to their benefits and inadequacies. We propose a novel methodology in relieving the issue of exactness and execution of data combination of multimodal biometric frameworks. This methodology utilizes multilayer perceptron neural organizations in preparing and testing of the organization while additionally proposing the utilization of the most well-known utilized unique mark in biometric field.